Rethinking Artificial Intelligence (AI) in qualitative research - Abdul Rashid, Nor'ain; Jamil, Nurul Akma; Tan, Woei Ling (Kulliyyah of Nursing, IIUM, 2025)
Artificial intelligence (AI) is increasingly being integrated into qualitative research. While AI provides tools that claim to promise greater efficiency and productivity, it also raises vital concerns about methodological integrity, ethical conduct, and the maintenance of contextual depth. This paper explores the implications of AI for qualitative research. It seeks to address the ethical, methodological, and epistemological concerns associated with AI integration. It also aims to promote critical engagement with AI while upholding the foundational values of context-rich qualitative research. The article initially addresses the growing publicity that AI has received in studies and public discourse, focusing on inflated hopes and misconceptions. The central debate concerns the impacts of AI on qualitative research, such as the way it could improve analysis and transcription efficiency. However, the use of AI is not without issues related to ethics, bias, loss of interpretive depth, and over-reliance on automation. The article argues in favour of responsible, critical, and ethically aware use of AI in qualitative research. AI can be a valuable tool to support, but not replace, qualitative researchers. Its use must be governed by reflexivity, ethical sensitivity, and contextual knowledge to uphold the foundational values of qualitative inquiry.